Analisis Hasil Belajar Matematika Berbasis Multimedia Interaktif Melalui Pembelajaran Daring Kelas V SD Negeri Trangkil 01 Pati - Mei Ida Astuti; Qoriati Mushafanah; Iin Purnamasari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study was to analyze the learning outcomes of interactive multimedia-based mathematics through online learning. This type of research is phenomenological qualitative research, starting from paying attention and examining the focus of the phenomenon to be studied, looking at various subjective aspects of object behavior. Then carry out data mining by interviewing the object or informant and making direct observations. The research method used is descriptive. The results of the Mathematics Learning Analysis from practice questions about data collection and presentation materials using Interactive Multimedia in Online Learning at SD Negeri Trangkil 01 Pati showed that it had been carried out well and achieved an increase of 2%, initially the practice of learning questions 1 had an average value of 90 with very good criteria. In the practice of learning questions 2 the average value is 92.7 with very good criteria. The results of the questionnaire or questionnaire analysis of mathematics learning outcomes in online learning for fifth grade students at SDN Trangkil 01 Pati, there were 29 respondents who were filled out by students. By using interactive multimedia based on videos from YouTube, students become easy and fun in online learning.